Numerical studies of plasmonically coupled spherical nanoparticles via epsilon-near-zero metamaterials - Farah Amirah Mohd Faizal (Nanyang Technological University, 2021)
Epsilon-near-zero (ENZ) metamaterials have captivated intensive studies due to the realization of optical properties that enhances the emission of Colloidal Nanocrystals. Colloidal Semiconductor Nanocrystals such as Quantum Dot and Nanoplatelet have raised significant attention in research studies because of their unique properties. The ability to be tuned and control imparted by quantum confinement effects make them promising candidates in the application of chiral sensing, asymmetric catalyst, quantum optics and spintronics. These unique optical properties allow the fabrication of intricate heterostructures that are not possible with other quantum-confined nanostructures. Forster Resonance Energy Transfer (FRET) is a type of Non-Radiative Energy Transfer (NRET) process that happens when the donor transfers energy to an acceptor in close proximity and is widely used in areas of biochemical analysis, environmental monitoring, and disease diagnosis. The rate of energy transfer depends on various factors, such as the distance between acceptors and donors, spectral overlap between donor emission and acceptor absorption, fluorescence quantum yield of the donor, dipole orientation and also refractive index of the medium.